Cold Dark Matter in SUSY Theories. The Role of Nuclear Form Factors and the Folding with the LSP Velocity. - Kosmas, T. S.; Vergados, J. D. (HNPS Advances in Nuclear Physics, 2020)
The momentum transfer dependence of the total cross section for elastic scattering of cold dark matter candidates, i.e. lightest supersymmetric particle (LSP), with nuclei is examined. We find that even though the energy transfer is small (<100 keV) the momentum transfer can be quite big for large mass of the LSP and heavy nuclei. The total cross section can in such instances be reduced by a factor of about five. The spin induced cross section for odd-A nuclei is less reduced since the high multipoles tend to enhance the cross section as the momentum transfer increases (for LSP mass < 200 GeV). We present calculations of the event rates for a number of nuclear targets in a relatively wide phenomenologically allowed SUSY parameter space. These event rates are folded with a Maxwellian velocity distribution of the LSP consistent with its density hi the halos. We thus find that the event rates due to the Earth’s revolution around the sun can change by 25%. This factor seems to be quite independent of the other parameters of the theory. Event rates up to 80 Kg^-1y^-1 can be obtained in the parameter space considered.